Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.46657/ajresd.2019.1.1.6
|View full text |Cite
|
Sign up to set email alerts
|

A Control Method using Artificial Intelligence in Wind Energy Conversion System

Abstract: This work presents a field-oriented control (FOC) of active and reactive power applied on Doubly Fed Induction Machine (DFIM) integrated in wind energy conversion system (WECS). The main objective of this work is to compare the performances of energy produced by the use of two types of controllers ( PI regulator and the neural network regulator (NN)) in order to control the wind power conversion system to compare their precision & robustness against the wind fluctuation and the impact on the quality of pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 6 publications
(5 reference statements)
0
7
0
Order By: Relevance
“…Our study represents the architecture ''structure'' of regulating the voltage delivered by a PMSM driven by a wind turbine via gear box controlled by a PI regulator [4], this after we present the model of each part of the conversion chain and the results of wind variation influence on the stability of PMSM output voltage amplitude, Wind profile is modeled as a fractional scalar evolves over time [5,6]. PMSM supply a nonlinear load from the rectifier installed on the output of the conversion chain via a controlled power inverter.…”
Section: Description Of the Studied Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study represents the architecture ''structure'' of regulating the voltage delivered by a PMSM driven by a wind turbine via gear box controlled by a PI regulator [4], this after we present the model of each part of the conversion chain and the results of wind variation influence on the stability of PMSM output voltage amplitude, Wind profile is modeled as a fractional scalar evolves over time [5,6]. PMSM supply a nonlinear load from the rectifier installed on the output of the conversion chain via a controlled power inverter.…”
Section: Description Of the Studied Systemmentioning
confidence: 99%
“…It is here that the main advantage of fuzzy logic regulation resides, in fact this type of technique does not need to establish any model of the system [1][2][3]. A direct application to the APF capacitor voltage regulation [4,5,6,7] with their simulation, by MATLAB, applied to wind power conversion chain network [8,9] is represented in the case of a non-linear variable load conditions [6], after modeling, to show the effectiveness of this kind of regulators on electrical power quality and improve the reliability of the APF on wind power system harmonic reducing.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, the wind speed is stable and high throughout the year, which can be very useful when using cooling with natural convection, adding to this the humidity rate, which is close to zero throughout the year, which is an important factor in minimizing the cost of using stainless materials and anti-corrosion maintenance. On the other hand, the infrared radiation contributes in rapid degradation for PV for conversion, this is justified by a study done by [39] who found that the lifetime of a PV module (with an output power close to 50%) in open circuit condition in the Adrar region could be reduced to 4 years, which would have a significant impact on its amortization. However, according to a study on a TE module exposed to thermal cycles of +146 to -20°C every 60s on one side and the other side is maintained at a constant temperature of 23°C gives a reduction of 20% after 40,000 thermal cycles and drop to 97% at 45,000 cycles [40].…”
Section: Selection Of the Appropriate Steg System For The Adrar Rmentioning
confidence: 99%
“…The wind energy is one of the most significant and rapidly developing renewable energy sources in the world and it provides a clean energy resource, which is a promising alternative in the short term in Algeria. [7][8] The electric power supplier is working to ensure the quality of electric power, to get to increase service continuity, now the quality criteria have evolved with the development of electronic equipment, which takes a prominent place in the production, and transport of an electrical network. It will, in the future, complete their action by implementing electronic power devices at high speed response, recently developed and known by the name FACTS (Flexible Alternative Current Transmission System) for control networks [5].…”
Section: Introductionmentioning
confidence: 99%
“…FACTS systems (Flexible Alternative Current Transmission Systems) are fast control systems networks using the resources offered by the power electronics and control microelectronics were recently studied and realized [6][7][8][9][10][11]. The recent development of FACTS devices opens up new possibilities for more efficient network operations by continuous and rapid action on the various network parameters (phase, voltage, impedance).…”
Section: Introductionmentioning
confidence: 99%